Financial reporting by New Zealand charities: finding a way forward - Hooper, K; Sinclair, R; Hui, D; Mataira, K (Emerald Group Publishing Limited, 2008)
Purpose – Charities are becoming recognised as playing an important part in communities by furthering government’s social objectives through increasing support to disadvantaged members of society. As charities multiply in number, it becomes increasingly difficult for fund providers and contributors to determine which charity to support. In New Zealand there is a move towards providing public access to the financial accounts of charities to assist stakeholders in their decision making and to enhance transparency in charities. However, this assumes that these financial accounts are understandable by all stakeholders. This paper aims to identify four problems that limit the way forward for financial reporting by New Zealand charities. Design/methodology/approach – The first section of the paper comprises a review of the literature on charities’ financial accounts with a particular focus on the four problems identified above. The paper then reports the results of eight interviews with charitable organisations, auditors and academics that have expertise in charity financial reporting, with a particular emphasis on the four identified problems. Findings – There was agreement that unresolved, these four problems could limit the way forward in financial reporting by New Zealand charities. Some recommendations are proposed that suggest a way forward with regard to these problems, so that the users of the financial reports of charities may benefit. Research limitations/implications – Highlights a need for further research into these problems to identify the feasibility of the proposed recommendations. Originality/value – The enactment of the Charities Act 2005 in New Zealand and its requirement to include financial accounts on a publicly available register has raised the profile of the financial reports of charities. However, there has been limited research into the financial reporting by New Zealand charities, so this paper is a timely evaluation of four specific problems that could limit the way forward of financial reporting by New Zealand charities.
Keywords: Charities; Accounting; New Zealand; Non-profit organizations